The idea of international human rights law - Wheatley, Steven (Oxford : Oxford University Press, 2019)
What is international human rights law? This question is addressed in this volume as Steven Wheatley explores how different types of human rights - moral, political, and legal - should be understood and considers how the complex systems theory of human rights can help to resolve current human rights controversies.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 4, 2019).
Keywords: Human rights; International law and human rights; Law; International law